A Battery‐Less Arbitrary Motion Sensing System Using Magnetic Repulsion‐Based Self‐Powered Motion Sensors and Hybrid Nanogenerator. (12th July 2020) - Bhatta, Trilochan; Maharjan, Pukar; Salauddin, Md.; Rahman, M. Toyabur; Rana, SM Sohel; Park, Jae Yeong
Abstract: Self‐powered arbitrary motion sensors are in high demand in the field of autonomous controlled systems. In this work, a magnetic repulsion‐assisted self‐powered motion sensor is integrated with a hybrid nanogenerator (MRSMS–HNG) as a battery‐less arbitrary motion sensing system. The proposed device can efficiently detect the motion parameters of a moving object along any arbitrary direction and simultaneously convert low frequency (<5 Hz) vibrations into useful electricity. The MRSMS–HNG consists of a central magnet for the electromagnetic (EMG)–triboelectric (TENG) nanogenerator and four side magnets for motion sensors. Because all the magnets are aligned in the same magnetization direction, the repulsive force owing to the movement of the central magnet actuates the side magnets to achieve self‐powered arbitrary motion sensing. These self‐powered motion sensors exhibit a high sensitivity of 981.33 mV g −1 under linear motion excitation and have a tilting angle sensitivity of 9.83 mV deg −1 . The proposed device can deliver peak powers of 27 mW and 56 µW from the EMG and TENG, respectively. By integrating the self‐powered motion sensors and hybrid nanogenerator on a single device, real‐time wireless transmission of motion sensor data to a smartphone is successfully demonstrated, thus realizing a battery‐less arbitrary motion‐sensing system for future autonomous control applications. Abstract : A battery‐less self‐powered arbitrary motion sensing system is developed by integrating self‐powered motion sensors and hybrid nanogenerators on a single device. A magnetic repulsion phenomenon is introduced, which enables self‐powered detection of diverse motion parameters with high accuracy and sensitivity. With the harvested energy, it is possible to transmit motion data to the smartphone wirelessly, showing applicability in autonomous control applications.